PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DAN MEDIA SOSIAL TERHADAP PRESTASI BELAJAR MAHASISWA STMIK SINAR NUSANTARA - Ari Wibowo; R Arie Febrianto (STMIK Sinar Nusantara, 2020)
The objectives of this study are : (1) To measure and test the effect of the use of information technology and social media on student achievement in STMIK Sinar Nusantara Surakarta. (2)To measure and test the interaction of the use of information technology and social media on student achievement in STMIK Sinar Nusantara Surakarta. The number of samples in this study were 50 respondents, with. The sampling technique uses purposive sampling.The results of the regression analysis found that there is a positive and significant influence of the use of information technology and social media on the learning achievement of students majoring in STMIK Sinar Nusantara Surakarta.T test and F test results prove that the information technology and social media variables have a positive and significant effect both partially and simultaneously on learning achievement. Based on the coefficient of determination which has a positive value of 0.397 shows that the learning achievement of students of the STMIK Sinar Nusantara Surakarta can be explained by the information technology and social media variables by 39.7%, while the remaining 60.3% is explained by other factors which was not observed in this study.Keywords: information technology, social media, learning achievement and regression